‘There’s a spirit of celebration…’: ‘A book about Finland’ by Lyudmila Kol - Łucewicz, Ludmiła (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper is dedicated to the theme of a holiday in the book ‘Where the Pine Trees Ring’ written by a Russian author Lyudmila Kol, nowadays a resident of Finland. In general, the book represents an autobiographical text that is notable for its many-sidedness and variety. The writer narrates in a delicate manner, but not without irony “about the country where the Finns live,” about the Finns themselves, the Finnish soul, about what is “hidden under the mask of a modern lifestyle.” The Russian author notices that the yearly life of modern Finns (very businesslike and dynamic) is organized according to various family celebrations. Religious, national, and local holidays occupy a considerable place in the book. There are comments about Palm Sunday, Juhannuspäivä, the Harvest Festival, the Independence Day, Christmas, the Sweden Day, about Pancake Week, Runeberg Day (birthday of the national poet) and others. The holidays presented in the text reflect the peculiar features of the Finns’ consciousness and their way of thinking, as well as the Russian author’s perception thereof and her attitude towards them.